Physiology of aging. (February 2019) - Hahr, Jung Y.
Abstract: In a natural state, death of the neuronal cells of the central nervous system is a hallmark of the aging process and occurs very insidiously. As we age, a natural loss of the body water occurs simultaneously with a rise in plasma osmolality. When a progressive rise in plasma osmolality occurs with age, it increases the effective viscosity of the circulating blood, and the thickened blood fails to perfuse the body systems and organs. If red blood cells fail to perfuse the central nervous system, the neuronal cells die from hypoxia and a lack of essential nutrients. This process is insidious but unavoidable. Hyperosmolality occurs in all mammals and it is a natural phenomenon of mammalian aging.